Verification of the efficacy of the gentamicin, tylosin, lincomycin, and spectinomycin antibiotic cocktail on frozen bovine semen - Frank V. Pellegrini; Emily A. Caflisch; Nicole A. Aulik (Journal of Dairy Science)
ABSTRACT: Artificial insemination (AI) is a common method used internationally for breeding cattle but may have the potential to introduce pathogenic bacteria to naïve populations during the process. Certain bacterial pathogens, such as Mycoplasmopsis bovis, have been a priority for disease transmission control and prevention via bovid semen for certain countries. One such method to prevent the transmission of infectious agents during the AI process has been prophylactically adding antimicrobials to both the neat and extended semen to kill or inhibit bacterial growth. A study published in 1988, detailed a method using a combination of gentamicin, tylosin, lincomycin, and spectinomycin (GTLS) as a means of controlling certain pathogenic bacteria in extended bovine semen. This was widely adopted and is still in use today, with Certified Semen Services making it required for their members. Publications since 1988 have provided evidence against the efficacy of the GTLS cocktail, arguing that M. bovis specifically is not being adequately controlled. Along with globally increasing antimicrobial resistance, a verification of the efficacy of the GTLS cocktail was warranted. Here the authors spiked various strains of bacteria into bovine GTLS-extended semen and quantified the bactericidal and bacteriostatic effect using bacterial culture. Our results demonstrate that multiple strains of Campylobacter fetus subspecies venerealis and Histophilus somni as well as one strain each of Ureaplasma diversum and Leptospira interrogans were effectively killed by the GTLS cocktail. However, the GTLS cocktail had only a bacteriostatic effect on several strains of M. bovis.